2018
DOI: 10.3389/fpsyt.2017.00311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endurance Exercise Modalities on Arterial Stiffness in Patients Suffering from Unipolar Depression: A Randomized Controlled Trial

Abstract: BackgroundPsychiatric disorders are associated with a higher prevalence of cardiovascular disease and mortality. Regular exercise has been shown to reduce depressive symptoms and improve arterial stiffness as a biomarker of cardiovascular risk. We aimed to investigate the effects of different exercise modalities on depression severity index and arterial stiffness in patients suffering from unipolar depression.Methods34 patients suffering from unipolar depression [female: 25, male: 9, age: 37.8, Beck-Depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 55 publications
1
18
0
9
Order By: Relevance
“…Previously published findings from our research group suggest that similar improvements occur in cardiorespiratory fitness (VO 2 max), cardiovascular health markers (blood pressure, arterial stiffness), and depressive symptomatology in patients with MDD who participated in 12 sessions of SIT or CAT (23, 24). These promising findings notwithstanding, some scholars doubt whether HIIT or SIT are appropriate training protocols for largely physically inactive populations (25, 26).…”
Section: Introductionsupporting
confidence: 52%
“…Previously published findings from our research group suggest that similar improvements occur in cardiorespiratory fitness (VO 2 max), cardiovascular health markers (blood pressure, arterial stiffness), and depressive symptomatology in patients with MDD who participated in 12 sessions of SIT or CAT (23, 24). These promising findings notwithstanding, some scholars doubt whether HIIT or SIT are appropriate training protocols for largely physically inactive populations (25, 26).…”
Section: Introductionsupporting
confidence: 52%
“…Exercise training regimes have also been shown to reduce depression symptoms and improve CV risk factors in patients with major depression [106,107]. A random effects meta-analysis of 25 RCTs (n=1,487 people with depression) showed that exercise interventions produced an overall large antidepressant effect, even after adjusting for publication bias (SMD=1.1, 95% CI=0.79, 1.43) [108].…”
Section: Physical Activity Approachesmentioning
confidence: 99%
“…Helgadttir et al 31 found that the Montgomery and Asberg Depression Rating Scale (MADRS) scores of depressive patients (18‐67 years) were significantly lower after low‐intensity aerobic exercise compared with moderate‐ or high‐intensity aerobic exercises (three times a week for 12 weeks); therefore, the author believed that moderate‐ and high‐intensity aerobic exercises are more effective than the low‐intensity one. Another study reported on short‐term (4 weeks, three times a week), high‐intensity (80% VO 2max ), and low‐intensity (60% VO 2max ) bicycling exercises in patients with unipolar depression, and found that the Beck Depression Inventory‐II (BDI‐II) score was decreased by 85% after high‐intensity exercise 32 . Trivedi et al 33 explored the effects of 12‐week high‐intensity walking (16 kcal/kg/wk) and low‐intensity walking (4 kcal/kg/wk) on depression, and the Hamilton Depression Scale (HDRS) showed that both of them achieved significant improvement in depression ( P < .001), and intensive exercise was more conducive to reducing depression levels.…”
Section: Evidence Of Exercise Effect On Depressionmentioning
confidence: 99%